Buckwheat (Fagopyrum esculentum Moench.) as an emerging companion crop in annual cropping systems: a systematic review - Virili, Alessandra; Marusig, Daniel; Delle Vedove, Gemini; Marraccini, Elisa (Italian Journal of Agronomy, 2024)
Sustainable intensification is considered an efficient alternative to conventional agriculture to feed a growing population while maintaining and benefitting the environment. Intercropping is one of the most studied practices to obtain production gains and other ecosystem services. Most intercrops involve legumes and cereals, but other species combinations should be explored to further increase the diversity of intercropping systems. Buckwheat (Fagopyrum esculentum Moench.; Polygonaceae) is an emerging minor crop which is gaining attention in alternative intercropping systems. This review provides a comprehensive view of the state of the art on the role of buckwheat as a companion crop in arable cropping systems. Despite buckwheat being well-known for its weed-suppressive ability, intercropping using buckwheat for weed control has received little attention. Few crops have so far been considered in relation to the introduction of buckwheat in annual cropping systems. This review uncovers a largely untapped research field involving buckwheat. The research perspectives are multiple as buckwheat consumption is increasing and its attractive flower resources and rapid growth offer the provision of several agro-ecosystem services that directly and indirectly benefit crop yield stability.